2017
DOI: 10.1261/rna.059592.116
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27b functions as a new inhibitor of ovarian cancer-mediated vasculogenic mimicry through suppression of VE-cadherin expression

Abstract: Aggressive cancer cells gain robust tumor vascular mimicry (VM) capability that promotes tumor growth and metastasis. is aberrantly overexpressed in vasculogenic cancer cells and regarded as a master gene of tumor VM. Although microRNAs (miRNAs) play an important role in modulating tumor angiogenesis and cancer metastasis, the miRNA that targets expression in cancer cells to inhibit tumor cell-mediated VM is enigmatic. In this study, we found that miR-27b levels are negatively co-related to expression in ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Recently, increasing studies demonstrated that the roles of miR‐27b are completely different in different type cancers and vascular diseases 144, 145, 146, 147. A study showed that miR‐27b improves angiogenesis in impaired bone marrow‐derived angiogenic cells (BMAC) in vitro and in vivo in type 2 diabetic mice via directly inhibiting the expression of thrombospondin‐1 (TSP‐1), p66 (shc) and Semaphorin6A (Sema6A), thereby improving the topical cell therapy of diabetic BCACs on wound healing and increasing the wound perfusion and capillary formation 144.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, increasing studies demonstrated that the roles of miR‐27b are completely different in different type cancers and vascular diseases 144, 145, 146, 147. A study showed that miR‐27b improves angiogenesis in impaired bone marrow‐derived angiogenic cells (BMAC) in vitro and in vivo in type 2 diabetic mice via directly inhibiting the expression of thrombospondin‐1 (TSP‐1), p66 (shc) and Semaphorin6A (Sema6A), thereby improving the topical cell therapy of diabetic BCACs on wound healing and increasing the wound perfusion and capillary formation 144.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…Overexpression miR‐27b reduces the proliferation, migration and tube formation of HUVECs and decreases angiogenesis in colorectal cancer and gastric cancer via inhibiting the VEGFC/VEGFR2 signalling 147, 148. Moreover, a recent study indicated that miR‐27b effectively represses migration and tube formation of ovarian cancer cells, and angiogenesis in vivo by inhibiting VE‐cadherin 145. In the bladder, prostate and colon tumours, miR‐27b plays anti‐tumour and anti‐angiogenesis roles 147, 149.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies discovered the affiliation of miRNAs to the cancers driving genes in tumor initiation and progression. For example, miR.125b, miR.145, miR.21 and miR.155 are known to be involved in breast cancer [6] and, miR.27b and miR.181d are known to be involved in ovarian cancer [7][8].…”
Section: Introductionmentioning
confidence: 99%